PARASOCIAL LANGUAGE IN INFLUENCER MARKETING: EFFECTS ON EMOTIONAL ENGAGEMENT AND PURCHASE INTENTION - Rosli, Nuraina Nadiah; Zulkifli, Zulfati Izazi (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2025)
In the evolving landscape of digital marketing, influencers have emerged as powerful intermediaries between brands and consumers, often using parasocial language an informal, conversational style of communication to engage audiences on a more personal level. Despite its widespread use, limited research has examined how parasocial language specifically affects emotional engagement and purchase intention, particularly within the Malaysian context. This study addresses this gap by proposing a conceptual framework that investigates the effects of parasocial language used by influencers on consumers’ emotional engagement and subsequent intention to purchase endorsed products. The primary aim is to explore the psychological mechanisms through which influencer communication strategies impact consumer behavior. Employing a quantitative research design, the study proposes the use of a structured questionnaire survey targeting Malaysian social media users aged 18–40. Data is intended to be analyzed using SPSS for preliminary testing and Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the measurement and structural models. Preliminary insights from the proposed framework suggest that parasocial language enhances emotional engagement, which in turn positively influences purchase intention. The findings offer both theoretical and practical contributions by extending the application of parasocial interaction theory to marketing communication and by guiding marketers and influencers on how to craft more effective, emotionally resonant messages. However, as a conceptual paper, it is limited by the absence of empirical data, and future studies are encouraged to validate the model using real-world samples and to explore additional variables such as influencer credibility and platform type.